Temporal Variation Among Populations Of House Fly Musca Domestica (Diptera: Muscidae) - SAUMYA SRIVASTAVA; RASHMI SINGH; R. R. TEWARI (International Journal of Pharma and Bio Sciences, 2012)
Three natural populations of house fly Musca domestica were analyzed for eight genetic loci by means of polyacrylamide gel electrophoresis (PAGE). Allozyme analysis at eight loci scores nineteen putative alleles. The amount of mean observed heterozygosity (Ho) was greater for Varanasi population than the other two populations studied. Nei’s genetic identity (I) and distance (D) values reveal that the house fly populations from Mirzapur and Varanasi are clustered closely (I=0.736) as compared to other two populations.